2017
DOI: 10.1007/s10530-016-1366-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic lineages of the invasive Aegilops triuncialis differ in competitive response to neighboring grassland species

Abstract: Competitive dynamics between native and exotic species can influence both the success of exotics in the novel environment as well as diversity and abundance of native species. Invasive species are often characterized by multiple introductions in the novel range, which can lead to population differentiation for invasion characteristics. Here we use two invasive lineages of the exotic grass, Aegilops triuncialis L., to determine if these lineages differ in their response to competitors and in their persistence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
(38 reference statements)
3
7
0
Order By: Relevance
“…In contrast, the East lineage was larger but stimulated less N ‐degrading enzyme activity (although the activity was sustained throughout the development stages), which also correlated with later flowering and production of fewer and larger seeds. Our results support previous work on this invasive species, which found that the East lineage is less affected by interspecific plant competition than the West (Gomola et al, ). We argue that these two lineages follow distinct strategies whereby the West lineage is successful spreading and establishing in open biotope space (i.e., bare soil gaps with fewer competitive neighbors and serpentine sites; Meimberg et al, ) while the East has a more competitive strategy to establish and persist within plant communities with more competitors (Gomola et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast, the East lineage was larger but stimulated less N ‐degrading enzyme activity (although the activity was sustained throughout the development stages), which also correlated with later flowering and production of fewer and larger seeds. Our results support previous work on this invasive species, which found that the East lineage is less affected by interspecific plant competition than the West (Gomola et al, ). We argue that these two lineages follow distinct strategies whereby the West lineage is successful spreading and establishing in open biotope space (i.e., bare soil gaps with fewer competitive neighbors and serpentine sites; Meimberg et al, ) while the East has a more competitive strategy to establish and persist within plant communities with more competitors (Gomola et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Our results support previous work on this invasive species, which found that the East lineage is less affected by interspecific plant competition than the West (Gomola et al, ). We argue that these two lineages follow distinct strategies whereby the West lineage is successful spreading and establishing in open biotope space (i.e., bare soil gaps with fewer competitive neighbors and serpentine sites; Meimberg et al, ) while the East has a more competitive strategy to establish and persist within plant communities with more competitors (Gomola et al, ). The ability to stimulate soil enzyme activity has a functional role that mediates these different strategies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…, Gomola et al. ) on plant fitness, and to influence community composition of soil biota (Schweitzer et al. , Nelson and Karp , Lamit et al.…”
Section: Introductionmentioning
confidence: 99%
“…Because many studies of invasive species assume that no intraspecific variation exists in their interactions with the environment and resident community, this can result in misleading insights and management recommendations, particularly if different genotypes employ different mechanisms of invasion (Meyerson and Cronin , Gomola et al. ).…”
Section: Introductionmentioning
confidence: 99%